Developing a Local Socio Scientific Issues-Based Biology Module Using the RQA Approach for Environmental Change - A Aida Ariya; Muhiddin Palennari; Nurhayati B; Firdaus Daud; Alimuddin Ali (Sakura Digital Nusantara, 2026)
Purpose: This study was conducted to design a Biology module grounded in local Socio Scientific Issues (SSI) and integrated with (RQA) approach for environmental change topics. It also aimed to evaluate the module’s validity, practicality, and effectiveness in facilitating Biology learning at the senior high school level. Methods: This research employed a Research and Development (R&D) design adapted from the Borg and Gall development model. The study was conducted at UPT SMA Negeri 2 Sinjai with 59 tenth-grade students and two Biology teachers. Data collection was carried out using expert validation instruments, practicality questionnaires completed by teachers and students, and learning achievement tests administered through pretest and posttest. The collected data were then analyzed using Gregory’s content validity coefficient to determine validity, percentage analysis to assess practicality, and N-Gain analysis to measure the increase in students’ learning outcomes. Findings: The developed module achieved a Content Validity coefficient of 1.00, which reflects a very high level of validity. This result was supported by the strong ratings given by both validators across all 35 assessed indicators. In terms of practicality, the module received an average score of 94% from teachers and 89% from students, placing both results in the highly practical category. Furthermore, the effectiveness evaluation produced an average N-Gain score of 0.77, which falls within the high category, with 73% of students demonstrating a high level of learning improvement. Research Implications: The module can be used as an alternative contextual teaching material that supports active learning and improves students’ understanding of environmental change. Originality: This study offers a locally contextualized Biology module that uniquely integrates SSI with the RQA approach to connect biological concepts with real environmental issues.